2015
DOI: 10.1002/jgt.21864
|View full text |Cite
|
Sign up to set email alerts
|

Local Clique Covering of Claw-Free Graphs

Abstract: Abstract:A k−clique covering of a simple graph G is a collection of cliques of G covering all the edges of G such that each vertex is contained in at most k cliques. The smallest k for which G admits a k−clique covering is called the local clique cover number of G and is denoted by lcc(G). Local clique cover number can be viewed as the local counterpart of the clique cover number that is equal to the minimum total number of cliques covering all edges. In this article, several aspects of the local clique coveri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…[9].) Concerning local clique cover number, R. Javadi et al showed in [12] that if G is a claw-free graph then lcc(G) ≤ c ∆(G) log(∆(G)) , for a constant c. In this section, we are going to prove that Conjecture 3 does hold for claw-free graphs.…”
Section: Claw-free Graphsmentioning
confidence: 88%
“…[9].) Concerning local clique cover number, R. Javadi et al showed in [12] that if G is a claw-free graph then lcc(G) ≤ c ∆(G) log(∆(G)) , for a constant c. In this section, we are going to prove that Conjecture 3 does hold for claw-free graphs.…”
Section: Claw-free Graphsmentioning
confidence: 88%
“…Our work is organized as follows. Section 2 contains our main results on ecc(G), where we improve upon the previously best known bound of ecc(G)cn43log13 n if α(G)=2, given by Javadi, Maleki, and Omoomi [8]. We also show how our results can be used to obtain even better bounds for fractional edge clique covers.…”
Section: Introductionmentioning
confidence: 66%
“…Notice that this problem is related to the local biclique cover problem where one is only interested in minimizing the number of distinct bicliques covering each node without minimizing the total number of bicliques [16]. Clearly, if a graph satisfies the ( f L , f R , k)-biclique cover condition it also satisfies the (max( f L , f R ))-local biclique cover condition, but the converse is not always true.…”
Section: Model I: a Node Belongs To A Small Number Of Bicliquesmentioning
confidence: 99%
“…Finally, a problem related to our work here, is the local biclique cover problem [16], where for a given (not necessarily bipartite) graph G and a parameter f we want to determine whether there exists a biclique cover of the edges of G (using an arbitrary number of bicliques) in which each node belongs to at most f bicliques. Arora et al [17] studied a generalization of clique cover with applications to community detection where nodes are limited to participate in a few cliques.…”
Section: Introductionmentioning
confidence: 99%